Cultural tourism and social resilience. Discourse of historic cities in East Germany, the case of Gotha and Eisenach. - Sung, Younkyoung (My University, 2020)
This thesis explores how cultural heritage plays a role in the development of urban identity by engaging both actively and passively with memory, i.e. remembering and forgetting. I argue that architectural heritage is a medium where specific cultural and social decisions form its way of presentation, and it reflects the values and interests of the period. By the process of remembering and forgetting, the meanings between inhabitant and object in urban environment are practiced, and the meanings are created. To enable the research in narrative observation, cultural tourism management is chosen as the main research object, which reflects the alteration of interaction between the architectural heritage and urban identity. Identifying the role of heritage management, the definition of social resilience and the prospects of cultural heritage as a means of social resilience are addressed. Case region of the research is East Ger- many, thereby, the study examines the distinct approaches and objectives regarding heritage management under the different political systems along the German reunification process. The framework is based on various theoretical paradigms to investigate the broad research questions: 1) What is the role of historic urban quarters in the revitalisation of East German towns? 2) How was the transition processed by cultural heritage management? 3) How did policy affect residents’ lives? The case study is applied to macro level (city level: Gotha and Eisenach) and micro level study (object level: specific heritage sites), to analyse the performance of selective remembering and making tourist destination through giving significance to specific heritage. By means of site observations, archival research, qualitative inter- views, photographs, and discourse analysis on printed tourism materials, the study demonstrates that certain sites and characteristics of the city enable creating and focusing messages, which aids the social resilience. Combining theory and empirical studies this thesis attempts to widen the academic discussion regarding the practice of remembering and forgetting driven by cultural heritage. The thesis argues for cultural heritage tourism as an element of social resilience and one that embraces the historic and cultural identity of the inhabitants.

Die Arbeit untersucht, wie das kulturelle Erbe bei der Entwicklung der städtischen Identität eine Rolle spielt, indem es sich aktiv und passiv mit dem Gedächtnis beschäftigt, z.B. dem Erinnern und Vergessen. Der Autor argumentiert, dass das architektonische Erbe ein Medium ist, in dem bestimmte kulturelle und soziale Entscheidungen seine Darstellungsweise bestimmen und dass es die Werte und Interessen dieser Zeit widerspiegelt. Durch den Prozess des Erinnerns und Vergessens werden die Bedeutungen zwischen Bewohner und Objekt im städtischen Umfeld eingespielt und die Bedeutungen werden geschaffen. Um die Forschung in der narrativen Beobachtung zu ermöglichen, wird das Kulturtourismusmanagement als Hauptforschungsobjekt ausgewählt, das die Veränderung der Interaktion zwischen dem architektonischen Erbe und der städtischen Identität widerspiegelt. Die Rolle des Kulturerbes, die Definition der sozialen Resilienz und die Perspektiven des kulturellen Erbes als Mittel der sozialen Resilienz werden angesprochen. Fallregion der Forschung ist Ostdeutschland, dabei untersucht die Studie die unterschiedlichen Ansätze und Ziele hinsichtlich des Kulturerbemanagements unter den verschiedenen politischen Systemen im deutschen Wiedervereinigungsprozess. Der Rahmen basiert auf verschiedenen theoretischen Paradigmen, um die breiten Forschungsfragen zu untersuchen: 1) Welche Rolle spielen historische Stadtviertel bei der Revitalisierung ostdeutscher Städte? 2) Wie wurde der Übergang zur Verwaltung des Kulturerbes durchgeführt? 3) Wie hat sich die Interaktion zwischen Politik und Bewohnern verändert? Die Fallstudie wird auf Makroebene (Stadtebene: Gotha und Eisenach) und Mikroebene (Objektebene: spezifische Kulturerbestätten) angewendet, um die Leistung von selektivem Erinnern und Erstellen von Reisezielen zu analysieren. Anhand von Standortbeobachtungen, Archivrecherchen, qualitativen Interviews, Fotografien und Diskursanalysen zu gedruckten touristischen Materialien zeigt die Studie, dass bestimmte Orte und Merkmale der Stadt die Schaffung und Verbreitung von Botschaften ermöglichen, die die soziale Widerstandsfähigkeit unterstützen. Durch die Kombination von Theorie und empirischen Studien wird versucht, die akademische Diskussion über die Praxis des Erinnerns und Vergessens im Bezug auf kulturelles Erbe zu erweitern. Abschließend wird für den Kulturtourismus als Element sozialer Resilienz argumentiert, das die historische und kulturelle Identität der Bewohner mit einbezieht.
Kulturtourismus und soziale Resilienz. Diskurs historischer Städte in Ostdeutschland, der Fall von Gotha und Eisenach.
Keywords: Fremdenverkehr; Fremdenverkehrspolitik; Historische Stadt; Standortmarketing; Kulturerbe; Stadtentwicklung; Resilienz; Fremdenverkehrsforschung; Empirische Untersuchung; Befragung; Tourismuspolitik; Städtetourismus; Denkmalschutz; Räumliche Identität